Philosophic-praxeological dimension of music education in Ukraine: formulation of the problem - Гнатів, З. Я. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
The article posing the problem of studying current issues of music education in Ukraine at the angle of philosophical and praxeological link. The musical education is considering as a system of theoretical, methodological and axiological doctrines that establish the relationship of art, pedagogy, philosophy, culture and defining social role and importance of music in existence through the prism of community interests and needs.